Evaluating Dental Health of Trainees in Correction Center of Tehran Province in 2008 - Saeedeh Sadr (Disease and Diagnosis, 2015)
Background: For planning in health,preventing and representing valuable dentistry services, we need to identify and evaluate the information on the status of individuals' dental hygiene and health. In this examination, evaluating dental health which is one of hygienic main and key problems has been conducted according to world's standards in correction center of Tehran province in 2008.. Methods: The examination was performedbased on the suggested standards of World Health Organization (WHO). The mission team sent to this center includes senior students of dentistry who divided into two (examiner and coder) groups. These students examined190 persons (172 male and 18 female) and filled the relevant form. After collecting information and filling examination forms, the statistical analysis was carried out and the results were reported. Results: The DMF index was 6.3 in the studied population. The values for females and males were 6.9 and 6.2, respectively. D, M and F indexes were3.69, 1.89 and 1.72, respectively. About13% of samples were caries free and dental Hypoplasiawas detected in 11% of samples and fluorosiswas observed in 2%. The most required treatment were filling one surfaceand fillingcomplicated and pull a tooth: 27.2%, 8.5% and 6%, respectively. Conclusions: DMF index was averagely lower than 4 which represented low levels of dentistry hygiene.Only 13% of samples were caries free which represented the preventive services weakness of mouth health.Therefore, it is necessary to perform special program for the purpose of WHO about DMFT rate.